A Comprehensive Review of the Mechanical Behavior of Suspension Bridge Tunnel-Type Anchorage - Yafeng Han; Xinrong Liu; Ning Wei; Dongliang Li; Zhiyun Deng; Xiangchao Wu; Dongshuang Liu (Advances in Materials Science and Engineering)
The recent surge of interest towards the mechanical response of rock mass produced by tunnel-type anchorage (TTA) has generated a handful of theories and an array of empirical explorations on the topic. However, none of these have attempted to arrange the existing achievements in a systematic way. The present work puts forward an integrative framework laid out over three levels of explanation and practical approach, mechanical behavior, and calculation method of the ultimate pullout force to compare and integrate the existing findings in a meaningful way. First, it reviews the application of TTA in China and analyzes its future development trend. Then, it summarizes the research results of TTA in terms of load transfer characteristics, deformation characteristics, failure modes, and calculation of ultimate uplift resistance. Finally, it introduces four field model tests in soft rock (mainly mudstone formations), and some research results are obtained. Furthermore, it compares the mechanical behavior of TTA in hard rock strata and soft rock strata, highlighting the main factors affecting the stability of TTA in soft rock formation. This paper proposes a series of focused topics for future investigation that would allow deconstruction of the drivers and constraints of the development of TTA.